2017
DOI: 10.1111/dme.13519
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in glycaemic control, hypoglycaemia and diabetic ketoacidosis according to socio‐economic status and area‐level deprivation in Type 1 diabetes mellitus: a systematic review

Abstract: Aim The aim of this systematic review was to examine the associations of individual-level as well as area-level socioeconomic status and area-level deprivation with glycaemic control, hypoglycaemia and diabetic ketoacidosis in people with Type 1 diabetes mellitus.Methods Ovid MEDLINE was searched to identify relevant cohort, case-control or cross-sectional studies published between January 2000 and June 2015. Search results were screened by title, abstract and keywords to identify eligible publications. Decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 53 publications
3
66
0
Order By: Relevance
“…Lower SES and higher HbA1c levels were associated with higher rates of DKA‐related hospitalizations, which is in accordance with previous reports . A systematic review reported evidence that lower SES and higher area‐level deprivation was significantly associated with a higher frequency of DKA in the course of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lower SES and higher HbA1c levels were associated with higher rates of DKA‐related hospitalizations, which is in accordance with previous reports . A systematic review reported evidence that lower SES and higher area‐level deprivation was significantly associated with a higher frequency of DKA in the course of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review reported evidence that lower SES and higher area‐level deprivation was significantly associated with a higher frequency of DKA in the course of the disease. As explanation, a lower utilization of health services among socially deprived persons occurring even in countries with universal health care coverage such as Germany was discussed . Furthermore, higher HbA1c levels suggest poorer treatment adherence, often resulting in higher rates of hospitalization for DKA …”
Section: Discussionmentioning
confidence: 99%
“…We also found no significant association between SH and parental education or health insurance, both markers of socio‐economic status. This is consistent with the findings of a recent systematic review which found that neither health insurance nor education was consistently associated with either an increase or decrease in risk of hypoglycaemia among both children and adults with type 1 diabetes …”
Section: Discussionsupporting
confidence: 91%
“…Ethnicity and socioeconomic status (SES) are well‐established and closely linked risk factors for a range of health outcomes, including inequalities in diabetes outcomes (both acute and chronic) . Determining the relative contribution of genetic and cultural influences on health vs the fundamental fiscal ability to access and use necessary health care has proved difficult.…”
Section: Introductionmentioning
confidence: 99%